Comparative study of the locked intramedullary nail and Ender pins in the treatment of tibial diaphyseal fractures Estudo comparativo entre a haste intramedular bloqueada e os pinos de Ender no tratamento das fraturas diafisárias da tíbia - Marcos Hideyo Sakaki; Alberto Tesconi Crocci; Arnaldo Valdir Zumiotti (Clinics, 2007)
OBJECTIVE: To compare the locked, unreamed intramedullary nail with Ender pins in the treatment of open Gustilo grade I or II or closed tibial diaphyseal fractures of type A, B, or C2 of the AO classification. MATERIALS AND METHODS: Forty-four patients with unilateral tibial diaphyseal fractures were treated with intramedullary nails or Ender pins. Twenty patients were treated with an unreamed intramedullary nail with access via the patellar tendon with static locking. Twenty-four patients were treated with Ender pins introduced medially and laterally with respect to the tuberosity of the tibia. The main parameters analyzed were type of reduction, complications, union rate, deformities, joint mobility, pain, gait, effort capacity, presence of neurovascular disorders, and complaints related to the synthesis material. RESULTS: During 1 year of follow-up, the fractures of 90.0% of the patients with intramedullary nails and 95.7% of patients with Ender pins healed within an average of 21.5 weeks and 20.9 weeks, respectively. The significant findings were as follows: patients treated with Ender pins had less mobility of the subtalar joint; patients treated with intramedullary nails were more likely to have pain in the knee; both groups showed shortening of the tibia at the end of 1 year of treatment. CONCLUSIONS: The two methods are similar in the treatment of type A, B, and C2 tibial diaphyseal fractures. OBJETIVO: Comparar a haste intramedular bloqueada não-fresada com os pinos de Ender no tratamento das fraturas da diáfise da tíbia tipos A, B ou C2 da classificação AO, fechadas ou expostas graus I ou II de Gustilo. MATERIAIS E MÉTODOS: 44 pacientes com fratura unilateral da diáfise da tíbia, tratados com HIB ou com pinos de Ender. Vinte pacientes foram tratados com uma haste intramedular bloqueada não fresada por acesso através do tendão patelar e com bloqueio estático; vinte e quatro pacientes com pinos de Ender introduzidos medial e lateralmente à tuberosidade da tíbia. Principais parâmetros analisados: tipo de redução, complicações, consolidação, deformidades, mobilidade articular, dor, marcha, capacidade para esforços, distúrbios neuro-vasculares e desconforto pelo material de síntese. RESULTADOS: No seguimento de um ano, 90,0% das hastes intramedulares e 95,7% dos pinos Ender dos pacientes apresentaram consolidação da fratura com tempo médio de 21,5 e 20,9 semanas, respectivamente. Os achados significantes foram: mobilidade da articulação subtalar menor nos pacientes tratados com pinos de Ender; dor no joelho mais freqüente nos pacientes tratados com HIB; encurtamento da tíbia nos dois grupos ao final de um ano de tratamento. CONCLUSÕES: Os dois métodos são semelhantes no tratamento das fraturas da diáfise da tíbia tipos A, B e C2.